Antithesis and argument in the hymns of Ephrem the Syrian - Botha, P. J. (Hervormde teologiese studies, 1988)
This paper reflects research on the semantic structure of antitheses. The thesis being proposed is that the defining quality of antitheses was implemented by the Syrian church father Ephrem as a rhetoric technique to enhance the power of arguments in his hymns. Examples are being investigated to explain the function of antitheses in the surface structure of some of his arguments.